2010
DOI: 10.2174/138955710791112604
|View full text |Cite
|
Sign up to set email alerts
|

Lycorine and its Derivatives for Anticancer Drug Design

Abstract: Amaryllidaceae alkaloids are extensively studied for their biological activities in several pharmaceutical areas, including, for example, Alzheimer's disease for which galanthamine has already reached the market. Among this chemical family, lycorine displays very promising anti-tumor properties. This review first focuses on the chemical diversity of natural and synthetic analogues of lycorine and their metabolites, and then on mechanisms of action and biological targets through which lycorine and its derivativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
76
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 47 publications
1
76
0
Order By: Relevance
“…Although the targets or mechanisms of lycorine are still undefined, the dominant biological effects and low cytotoxicity of lycorine render it as a potential clinical drug or lead. For instance, it has received much attention as a promising anticancer agent for bladder cancer, cervical cancer, leukemia, prostate cancer, and multiple myeloma (14,(19)(20)(21)(22)(23). However, the defined molecular mechanisms underlying lycorine-regulated suppression of tumorigenesis remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Although the targets or mechanisms of lycorine are still undefined, the dominant biological effects and low cytotoxicity of lycorine render it as a potential clinical drug or lead. For instance, it has received much attention as a promising anticancer agent for bladder cancer, cervical cancer, leukemia, prostate cancer, and multiple myeloma (14,(19)(20)(21)(22)(23). However, the defined molecular mechanisms underlying lycorine-regulated suppression of tumorigenesis remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…In 1956, scientists determined the three-dimensional structure of lycorine by single crystal. Modern pharmacological research shows that lycorine has anti-inflammatory, inhibiting acetylcholinesterase, alkali resistant malaria, cardiovascular protection and a variety of tumor cell apoptosis induced by alkali, lycorine also has broad antiviral activity, such as SARS virus, herpes simplex virus, vaccinia virus, Punta Toro virus and Rift Valley fever virus [2][3][4] . On the other hand, the study of lycorine and its derivatives have also greatly promoted the progress in the treatment of diseases such as cancer, Alzheimer's disease, viral infection and other serious harm to human health [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Lycorine, known as a multifunctional compound, is extensively studied for its pharmacological activities, such as anti-tumor activity (Lamoral-Theys et al, 2010). Previous studies have shown that lycorine presented a potential anti-cancer activity in breast cancer via the inhibition of tumor growth and metastasis Ying et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the treatment for breast cancer, some adverse effects could cause serious complications and affect the health and quality of life among survivors (Odle, 2014). Therefore, it is necessary to develop novel anti-cancer candidates for breast cancer.In the past several decades, natural compounds such as resveratrol (Sinha et al, 2016), epigallocatechin-3-gallate, oldenlandia diffusa and Ziziphus jujube have been demonstrated that possessed potential anti-breast cancer activity (Bonofiglio et al, 2016).Lycorine, known as a multifunctional compound, is extensively studied for its pharmacological activities, such as anti-tumor activity (Lamoral-Theys et al, 2010). Previous studies have shown that lycorine presented a potential anti-cancer activity in breast cancer via the inhibition of tumor growth and metastasis Ying et al, 2017).…”
mentioning
confidence: 99%